HR Analytics: Trend from Data to Predictive Analysis for HR Professionals - Gupta, Megha; Srivastava, Nandini (International Journal of Psychosocial Rehabilitation, 2020)
Though the analytics function in the organization has shown an upsurge in its usage, especially in functions like sales, marketing, finance, and operations, its application and interest in the people function are still lagging behind and need a push. In this study the researcher primarily aims towards measuring the levels of usage of HR analytics. It has been diagnosed that the practice of HR metrics is still in its early phases and has a high scope of leveraging it to its full potential. Though HR professionals have a common consensus in agreeing on the importance of people metrics, at the same time they endorse the main hindrance in its implementation: the analytical skills gap. It is pertinent to note that, as per the concerned literature review, the global perception is optimistic. This paper seeks to discuss the paradigm shift from mere data presentation to taking proactive predictive decisions on people matters. Through this paper, the researcher has tried to gain awareness of the tradition of HR dashboards, data, analytics, and metrics. This research project enlarges the span of information on the theme of HR analytics being educational in nature and also comprehends the journey of people analytics as well as its current applications and a charter to leverage it further for the benefit of the establishment.